A Comparative Study of Propofol-Based Total Intravenous Anaesthesia and Isoflurane-Based Inhalational Anaesthesia on Clinical Variables During Recovery from Anaesthesia - Abdulkahar Sayadi (International Journal of Advanced Pharmaceutical Sciences and Research, 2026)
The process of recovery from general anaesthesia is much more than just a final step in surgical treatment – this is a densely medical period where various aspects such as pharmacology, airway protection, hemodynamics, patient comfort, and hospital performance are concentrated amid difficult conditions. In this paper, we present a comparative analysis of total intravenous anaesthesia with propofol (TIVA) and inhalational anaesthesia with isoflurane, paying particular attention to clinical parameters during the wake-up and recovery periods. The study involved 100 patients who underwent surgery and were randomly distributed into two groups. 50 people received anaesthesia based on propofol, while another 50 patients had anaesthesia based on isoflurane. The parameters studied included the time until the first response, eye opening, extubation, total recovery time, time in the post-anaesthesia care unit (PACU), changes in vital signs, postoperative nausea and vomiting (PONV), and postoperative shivering. According to the baseline characteristics, the two groups were comparable in many respects. Indicators of recovery in the case of propofol were better for all the studied periods: the first response was 7 plush 2 minutes in the propofol group compared to 15 plush 6 minutes in the isoflurane group; the eye opening was 8 plush 3 minutes compared to 18 plush 7 minutes; extubation was 6 plush 2 minutes compared to 12 plush 5 minutes; the total recovery period was 10 plush 4 minutes compared to 25 plush 8 minutes; PACU stay was 4 plush 3 minutes compared to 10 plush 6 minutes. The differences were significant (p greater then 0.05). The PONV and shivering were rarely observed in both groups and did not differ significantly. It can be concluded that TIVA with propofol might have advantages, including faster and easier recovery without additional risks.